Revolting things : an archaeology of shameful histories and repulsive realities - Mullins, Paul R., 1962- (University Press of Florida, 2021)
"In this book, Paul Mullins examines a wide variety of material objects and landscapes that induce anxiety, provoke unpleasantness, or simply revolt us, looking at the way the material world shapes how we imagine, express, and negotiate difficult historical experiences"--